Achieving early metabolic control in adults with type diabetes mellitus in Peru - Rocca Nación, Jesus (2023)
Objective: To estimate the rate of subjects with type 2 diabetes mellitus (T2DM) who reach the therapy goal for HbA1C one year after diagnosis (early metabolic control). Methods: This was a retrospective study reviewing clinical records of adults who came to sixteen health centers distributed in nine Peruvian cities. Patients who received an initial T2DM diagnosis and who had at least one-year follow-up were included. Metabolic goals set in ADA 29018 standards were considered.     Results: Four hundred and fifty-seven subjects (53,03% female) were included. When diagnosed, their mean age was 55,75 years (standard deviation [SD]: ± 12,92), and mean HbA1C value was 9,10% (SD: ± 2,28). Concomitant diagnosis including high blood pressure or dyslipidemia were found in 27,13% and 52,40% of all subjects, respectively. After one-year follow-up, 57,76% of all subjects achieved the HbA1C goal (<7,0%). Goal achievement for other parameters were 39,66% for LDL-C (<100 mg/dl), 55,56% for HDL-C in males (>40 mg/dL), 24,31% for HDL-C in females (>50 mg/dL), 48,24% for triglycerides (<150 mg/dL), and 89,23 for blood pressure (<140/90 mm Hg).   Conclusions: In this real-life study performed in T2DM adults and with one year follow-up, reaching an appropriate goal for HbA1c (<7%) was achieved by 58% of all subjects. Although these results are compatible with reports from nearby regions, an opportunity is evidenced for improving early goal achievement with the objective of obtaining better results in the short term.